Effectiveness and safety of Danshen injections in treatment of cardiac failure: a network meta-analysis - Song, Yuchen; Song, Nan; Jia, Lianqun; Pei, Yupeng (Frontiers in Pharmacology, 2024)
Objective: The purpose of this network meta-analysis (NMA) was to compare the therapeutic effects of various Danshen injections on heart failure to determine the optimal Danshen injection combined with conventional treatment.Methods: 8 databases were searched from the inception of these databases to May 2023 to collect randomized controlled trials (RCTs) on the effectiveness and safety of Danshen injections in the treatment of heart failure. This NMA was performed using Stata 16.0 software and R 4.1.3 software.Results: A total of 24 RCTs involving 2186 subjects were included. The intervention group received Danshen injections plus conventional treatment, involving the following 7 Danshen injections. The results of the NMA showed that Compound Danshen injection + Common (SUCRA: 79.6%) and Sodium tanshinone ⅡA sulfonate injection + Common (SUCRA: 78.0%) exhibited higher total effective rates.Sodium tanshinone ⅡA sulfonate injection + Common (SUCRA: 94.3%) and Danshen injection + Common (SUCRA: 68.2%) were superior to other traditional Chinese medicines in improving left ventricular ejection fraction (LVEF). Danshen injection + Common (SUCRA: 99.9%) and Shenxiong glucose injection + Common (SUCRA: 77.2%) were the most effective in reducing brain natriuretic peptide (BNP). In addition, compared with conventional treatment, all Danshen injections did not increase the risk of adverse reactions.Current evidence shows that all seven Danshen injections are effective for heart failure. Due to the limited quantity and quality of the included studies, our findings need to be verified by more high-quality studies.